2012
DOI: 10.1111/j.1582-4934.2011.01411.x
|View full text |Cite
|
Sign up to set email alerts
|

PED/PEA‐15 interacts with the 67 kD laminin receptor and regulates cell adhesion, migration, proliferation and apoptosis

Abstract: Phosphoprotein enriched in diabetes/phosphoprotein enriched in astrocytes-15 kD (PED/PEA-15) is an anti-apoptotic protein whose expression is increased in several human cancers. In addition to apoptosis, PED/PEA-15 is involved in the regulation of other major cellular functions, including cell adhesion, migration, proliferation and glucose metabolism. To further understand the functions of this protein, we performed a yeast two-hybrid screening using PED/PEA-15 as a bait and identified the 67 kD high-affinity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 52 publications
(85 reference statements)
1
22
0
Order By: Relevance
“…Further studies suggested that MGr1‐Ag/37LRP could promote MDR of GC cells via enhancing cell adhesion and then inhibiting drug‐induced apoptosis . Several studies indicated that 37LRP was involved in tumor development and progression . Moreover, an interaction between 37LRP and PrPc was first established in a two‐hybrid screening of a HeLa cDNA expression library for PrPc‐interacting proteins .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Further studies suggested that MGr1‐Ag/37LRP could promote MDR of GC cells via enhancing cell adhesion and then inhibiting drug‐induced apoptosis . Several studies indicated that 37LRP was involved in tumor development and progression . Moreover, an interaction between 37LRP and PrPc was first established in a two‐hybrid screening of a HeLa cDNA expression library for PrPc‐interacting proteins .…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17] Several studies indicated that 37LRP was involved in tumor development and progression. [18][19][20] Moreover, an interaction between 37LRP and PrPc was first established in a two-hybrid screening of a HeLa cDNA expression library for PrPc-interacting proteins. 22,36,37 The pathogenic relevance of 37LRP/67LR and PrPc interaction was revealed in tissues and cells of scrapie compared with nonscrapie-infected mice.…”
Section: Cancer Cell Biologymentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminal DED in PEA-15 has led to investigations into its role in regulating apoptosis [9,10,12]. More recently it has been discovered that PEA-15 has a diverse set of regulatory functions, including roles in proliferation, glucose metabolism, cell cycle control, cell adhesion, migration and autophagy and its expression has been shown to be altered in various cancers [9,10,[12][13][14].…”
Section: Discussionmentioning
confidence: 99%